Four-day delay “metachronous” polymicrobial necrotizing fasciitis of lower limbs: a unique case report - Guzmán, Álvaro; Benjumea, Antonio; Hernández-Mateo, Jose Maria; Sanz-Ruiz, Pablo; Vaquero, Javier (Acta Biomedica Atenei Parmensis, 2023)
Necrotizing fasciitis is a rare soft tissue infection that requires immediate medical attention to prevent its fulminant development that can lead to amputation or death of the patient. In most of reported cases of multifocal necrotizing fasciitis, injuries appear synchronously within hours from the initial diagnosis. It is the only third reported case with metachronous lesions, and the first that involves both S. pyogenes and S. aureus. Early diagnosis and multidisciplinary treatment is mandatory to prevent fatal outcomes. We present the case of a 58-year-old Caucasian man who developed necrotizing fasciitis of both lower limbs with four days between each one. After initial clinical suspicion, he was treated with intravenous antibiotics and we performed an urgent fasciotomy of the right leg and diagnosis was confirmed. Streptococcus pyogenes and Methicillin-Resistant Staphylococcus aureus were isolated from intraoperative cultures. Four days later, due to rising signs on the left limb, another fasciotomy had to be performed and the same microorganisms were isolated. Our patient was discharged home one month after his admission and had no complications during the follow-up. In order to prevent the development of metachronous lesions, early multidisciplinary treatment with aggressive and repeated debridement is necessary. We managed to keep our patient alive, without amputation or intervention by Plastic Surgery, and he recovered fully which is an excellent outcome from a very aggressive disease.